2015
DOI: 10.1016/j.ccell.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Action Combination Therapy Enhances Angiogenesis while Reducing Tumor Growth and Spread

Abstract: Increasing chemotherapy delivery to tumors, while enhancing drug uptake and reducing side effects, is a primary goal of cancer research. In mouse and human cancer models in vivo, we show that coadministration of low-dose Cilengitide and Verapamil increases tumor angiogenesis, leakiness, blood flow, and Gemcitabine delivery. This approach reduces tumor growth, metastasis, and minimizes side effects while extending survival. At a molecular level, this strategy alters Gemcitabine transporter and metabolizing enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
160
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(171 citation statements)
references
References 41 publications
2
160
1
4
Order By: Relevance
“…One of these factors is hypoxia. 28,29 Several studies have demonstrated that prolonged anti-angiogenic therapy increased the expression of mesenchymal phenotypes, [30][31][32][33] and this may be due to hypoxia induced by excessive anti-angiogenesis. Other studies have also shown that hypoxia and hypoxia-inducible factor-1 alpha (HIF-1α) promote EMT in several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…One of these factors is hypoxia. 28,29 Several studies have demonstrated that prolonged anti-angiogenic therapy increased the expression of mesenchymal phenotypes, [30][31][32][33] and this may be due to hypoxia induced by excessive anti-angiogenesis. Other studies have also shown that hypoxia and hypoxia-inducible factor-1 alpha (HIF-1α) promote EMT in several tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is crucial to include an imaging modality in studies investigating the effects of nanoparticle accumulation in vivo and to intervene if the therapy is inhibited by poor access to the tumor. Fortunately, an increasing number of methods to enhance the EPR effect in tumors have been developed, both in preclinical and clinical settings, including the use of heat to increase vessel permeability and induce extravasation of nanomedicine (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative arguments which attest CD8+ prevalence in LM suggest a stronger antitumor defense reaction in comparison to HCC. A possible explanation of enhanced CD8+ cells number in LM than in HCC may be related to the increased tumor angiogenesis in metastases [42][43][44] and to the intrinsic relationship between proangiogenic factors and TILs [45,46].…”
Section: Discussionmentioning
confidence: 99%